2020
DOI: 10.1108/jarhe-08-2020-0278
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral intention of “digital natives” toward adapting the online education system in higher education

Abstract: PurposeThe aim of the study is to examine the intention of students toward the online education system with emphasis on online examination in higher education. The study investigated different constructs that have an influence on the use of the online platform for learning to the specific domain that mitigates the personal needs of the learners outside the physical class boundaries.Design/methodology/approachData were collected through a self-administered structured questionnaire in a single cross-sectional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 76 publications
(78 reference statements)
4
10
0
Order By: Relevance
“…The findings showed that PU, PEU and ATT all had a favourable and significant effect on the respondents' intent to use OL. The results of the current study agree with those of other earlier investigations (e.g., Bag et al, 2022;Nasri et al, 2013). Consistent with the findings of the previous research by Nasri et al (2013) and Mart ınez-L opez et al (2020), the authors find that both PEU and PU show a positive connection with students' ATT; however, PU appeared to be a more robust predictor than PEU in the present research.…”
Section: Discussionsupporting
confidence: 93%
“…The findings showed that PU, PEU and ATT all had a favourable and significant effect on the respondents' intent to use OL. The results of the current study agree with those of other earlier investigations (e.g., Bag et al, 2022;Nasri et al, 2013). Consistent with the findings of the previous research by Nasri et al (2013) and Mart ınez-L opez et al (2020), the authors find that both PEU and PU show a positive connection with students' ATT; however, PU appeared to be a more robust predictor than PEU in the present research.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, results of the study establish the positive and significant role of perceived usefulness, perceived easiness of use and attitude towards technology on adaptation intention to online education. These findings also find support from few earlier contributions like Bag, et al. (2020).…”
Section: Implications Of the Studysupporting
confidence: 89%
“…The scales for perceived usefulness and perceived easiness of use are taken from the previous studies of Davis (1989) and Bag et al. (2020) with slight modification.…”
Section: Methodology Of the Studymentioning
confidence: 99%
“…According to Hair et al (2014), when the value of average variance extracted (AVE) is equal to or greater than 0.5 (Bag et al, 2020), it implies that the construct elucidates more than half of the variance of its items. Thus, the AVE values were also above the threshold limit (0.5), for all the constructs of this study, which means that the convergent validity is well established and it is also presented in Table 2.…”
Section: Measurement Of Reliability and Validitymentioning
confidence: 99%